Jewish migrations : past experiences and post-war prospects - Kulischer, Eugene M. (New York: American Jewish Committee, 1943)
"by Eugene M. Kulischer ; Research Institute on Peace and Post-war Problems of the American Jewish Committee Bibliotheek Camille Huysmans"